Hubungan Risiko Saham Dengan COVID-19 - Anggara, I Gde Wahyu Purna (E-Jurnal Akuntansi; Vol 33 No 3 (2023)DO - 10.24843/EJA.2023.v33.i03.p14, 2023)
COVID-19 has affected all aspects of life, including capital markets around the world, including Indonesia. This study aims to look at the impact of COVID-19 on changes in risk in stocks. Stock risks that are the object of research are overall risk (variance return) and market-based risk (stock beta). The research method used is a quantitative approach with a population of all company shares listed on the Indonesia Stock Exchange (IDX) with purposive sampling, where a sample of 67 companies was obtained. There is a significant difference between the total stock risk before the COVID-19 pandemic and during the COVID-19 pandemic. There is an increase in total stock risk during the COVID-19 pandemic. Furthermore, there is a significant difference between market risk before the COVID-19 pandemic and during the COVID-19 pandemic. Keywords: Stock; COVID-19; Return; Stock Risk